Home Based Cake Business Development Strategy Using Model Canvas Among ULAMM Clients at PNM Tangerang - Ninik Istichomah; Sri wahyuni (International Journal of Economics, Business and Innovation Research, 2026)
This study examines the implementation of the Business Model Canvas (BMC) in home-based cake businesses operated by ULaMM clients of PT Permodalan Nasional Madani (PNM) Tangerang Branch, as well as business development through SWOT analysis. The research adopts a descriptive qualitative approach and considers a specific time scope, focusing on business activities and strategic decision-making processes undertaken by home-based cake enterprises during 2024. Sampling was conducted using a purposive technique, involving informants directly related to the research objectives. A total of 12 informants were selected and analyzed to depict the Business Model Canvas of the enterprises. Data collection techniques included interviews, observations, and field notes. The application of the Business Model Canvas to home-based cake businesses of ULaMM clients at PNM Tangerang Branch indicates that the UMKM business models are structured and possess a solid foundation for continued development. Furthermore, the SWOT analysis integrated with the Business Model Canvas approach reveals that business development can be conducted more strategically through a comprehensive understanding of the strengths, weaknesses, opportunities, and threats faced by the UMKM actors